Influence of Nanoreinforced Particles (Al2O3) on Fatigue Life and Strength of Aluminium Based Metal Matrix Composite - Alalkawi, Hussain J. M; Hamdany, Aseel A.; Alasadi, Abbas Ahmed (Al-Khwarizmi Engineering Journal, 2017)
Abstract In this investigation, Al2O3 nano material of 50nm particles size were added to the 6061 Al aluminium alloy by using the stir casting technique to fabricate the nanocomposite of 10wt% Al2O3. The experimental results observed that the addition of 10wt% Al2O3 improved the fatigue life and strength of constant and cumulative fatigue. Comparison between the S-N curves behaviour of metal matrix (AA6061) and the nanocomposite 10wt% Al2O3 has been made. The comparison revealed that 12.8% enhancement in fatigue strength at 107cycles due to 10wt% nano reinforcement. Also cumulative fatigue life of 10wt% nanocomposite was found to be increased by 33.37% and 39.58% for low-high and high-low loading sequences, respectively, compared to the metal-matrix cumulative life. Keywords: Al2O3 nanoparticles, AA6061/10wt%, constant and cumulative fatigue, MMCs.